Struktur Hasil Translokasi Bangunan Vernakular Jawa Timur di Kampoeng Djawi Wonosalam - Bagaskara, Yohanes Vincent Mahendar; Yusran, Yusfan Adeputera (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2018)
Vernacular buildings in Indonesia, especially vernacular buildings of East Java, are increasingly diminishing. Many efforts have been made to maintain the existence of vernacular buildings, one of which is ex-situ conservation by re-using it adaptively as a tourist destination as found in Kampoeng Djawi Wonosalam. Translocation of vernacular buildings to new locations and new function causes changes in vernacular buildings, particularly in its structure. Changes occur as an adaption to new locations and new activities that will be accommodated. The objective of this paper is to describe the structural changes in vernacular buildings as the result of translocation. Qualitative descriptive method is used to find the structural changes, so the results obtained are actual facts. Changes that occur then analyzed with the concept of adaptive exoskeleton building. According to the results of observations and analysis, changes that occur in vernacular building translocation are caused by resilience, safety, and visual factors, as well as fulfillment of new activities.